2019
DOI: 10.1016/j.jpainsymman.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Psychoneurological Symptoms and Their Association With Longitudinal Cognitive Function and Quality of Life in Older Breast Cancer Survivors

Abstract: Context. Symptoms affect quality of life (QOL), functional status, and cognitive function in cancer survivors, but older survivors are understudied.Objectives. The objectives of this study were to identify prototypical presystemic therapy psychoneurological symptom clusters among older breast cancer survivors and determine whether these symptom clusters predicted cognition and QOL over time.Methods. Women with newly diagnosed nonmetastatic breast cancer (n ¼ 319) and matched noncancer controls (n ¼ 347) aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 51 publications
3
59
3
Order By: Relevance
“…Tometich et al (24), in a longitudinal study, investigated the effects of baseline anxiety and depression together with fatigue, pain and sleep disturbances on perceived and objective cognitive functions in 319 BC patients and 347 non-cancer controls, all aged ≥60 years. Although all groups showed improvements in neuropsychological scores over time, 16% of the patients who had high symptoms at baseline had lower perceived and objective cognition at that time point, and lower perceived cognition all along the observation time (24). Lower functional well-being at baseline predicted lower BC-specific QOL at all time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tometich et al (24), in a longitudinal study, investigated the effects of baseline anxiety and depression together with fatigue, pain and sleep disturbances on perceived and objective cognitive functions in 319 BC patients and 347 non-cancer controls, all aged ≥60 years. Although all groups showed improvements in neuropsychological scores over time, 16% of the patients who had high symptoms at baseline had lower perceived and objective cognition at that time point, and lower perceived cognition all along the observation time (24). Lower functional well-being at baseline predicted lower BC-specific QOL at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of previous findings on cognitive functioning after ET is complicated by the use of different methods (neuropsychological batteries, definitions of cognitive impairment or longitudinal decline, the involvement of BC or healthy controls), the confounding effects of various cancer treatments, the varying times of menopause, the patients' psychological status and treatment compliance and, many times small sample sizes (4,5). Limited experience is gained on old patients (2,16,23,24). Gaining knowledge on cancer therapy-induced cognitive impairment would yield practical implications.…”
mentioning
confidence: 99%
“…We selected the 8 symptoms/illnesses described above because they tend to cluster and/or include known treatment effects (eg, neuropathy) . We included myocardial infarction, congestive heart failure, arrhythmia, and angina as possible treatment‐toxicity–related.…”
Section: Methodsmentioning
confidence: 99%
“…These older survivors may be especially vulnerable to a high symptom burden, and their symptoms tend to affect functioning, given comorbidities and aging . We previously reported that presystemic therapy symptoms predicted 24‐month function . However, there are few data on changes in symptom burden over time in older survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation